Patient safety and medication errors (Italian Journal of Public Health, 2005)
The morbidity and mortality of drug-related problems has most recently been estimated to cost $177.4 billion annually within the United States alone. Empirical investigations have also suggested that almost one-fifth of all medical errors are drug-related within hospital settings, with over half of these being of a preventable nature. As such, minimizing medication errors has emerged as a priority area to ensure patient safety within healthcare systems worldwide, as several nations have implemented broad initiatives to improve the medication use system. Due to the numerous complexities involved, multifaceted and systemwide approaches to redesigning processes are most often advocated. Given the importance of appropriate medication use in achieving optimal patient outcomes, this paper addresses the various nomenclature and taxonomies of error within healthcare as well as the incidence, risk factors, causes, and prevention of medication errors.
Keywords: Patient safety; medication errors